Juridical Analysis of the Role of the Police in the Process of Investigating Unlicensed Mining Crimes - Putra, Richie; Erniyanti , Erniyanti (Journal of Multidisciplinary Academic and Practice Studies, 2026)
Purpose: This study aims to examine the legal framework regulating unlicensed mining crimes in Indonesia and the role of the police in investigating such offenses. Specifically, this research focuses on the jurisdiction of the Bintan Police and explores the challenges and solutions for investigating illegal mining activities. Research Methodology: This study adopts a normative juridical method, utilizing a literature review for legal analysis, and an empirical juridical approach, which includes field studies to collect data through interviews with law enforcement personnel and community members involved in illegal mining. Results: This study finds that while Law No. 3 of 2020 provides a legal basis for prosecuting unlicensed mining, the effectiveness of enforcement is hindered by challenges such as limited resources, complex geographic areas, a lack of public legal awareness, and local community involvement in illegal mining activities. Despite police efforts, illegal mining continues to increase in regions such as Bintan. Conclusions: The research concludes that enhancing police capacity through training, improving resources, and fostering better community engagement are essential to effectively combating illegal mining. Increased coordination between local and central authorities is also necessary to comprehensively address this issue. Limitations: This study is limited by its geographic focus on Bintan and the availability of data from local law enforcement agencies. Further research is needed in other regions for broader generalization Contributions: This study provides valuable insights into the operational challenges of law enforcement in tackling illegal mining and offers actionable recommendations for improving police effectiveness in such investigations